Territorialidade e identidade: a migração dos descendentes de italianos no município de Francisco Beltrão - Paraná - Briskievicz, Michele (2012)
The county of Francisco Beltrao is located in the Southwest of Parana. Its effective occupation has happened, from the inner migrations, from Rio Grande do Sul, Santa Catarina and Parana, and it has been intensified from 1940 on. It is a territory characterized by the significant presence of European descendents, specially the Italian ethnicity. It can be seen through their economic and cultural manifestation. Our objective on this research was to unveil the migratory dynamic of Italian people to the county and show the main characteristics instituted in the territory organization, considering the cultural and economical contributions echoed in the space organization, seen nowadays. To reach the expected results, it has been carried out the background of the region, mainly the county of Francisco Beltrao; It has been thought and understood the territorial approach and others concepts as social and territorial process of daily life organization; it has been checked the periods of bigger migratory flux, and at the same time it has been showed the migrants territory of origin, the trajectory gone through by the families, since the moment of immigration in Brazil and the reasons they have done it; at last, it has been analyzed the main economic and cultural changes that the families caused in the county identifying the identity characteristics linked to the ancestors, checking also, new habits and behaviors that have been incorporated. Through the results, it has been realized that the families contributed and still contribute in the territorial identity characterization of Francisco Beltrao, as well, reveals marks of Italian culture. It has been highlighted that these characteristics must bee reported, adding value to the history of family life that takes different values and express the social experiences happened in the time and space.